Судьба зимней вишни: [роман] / Людмила Зарецкая - Зарецкая Людмила (Хозяйка своей судьбы, 2015)
Экземпляры: СБ (201505) / Инвентарный номер: 50891 / Цена: 142.00 / Сис.шифр: Р2 / Авт.знак: З-34 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6